2020
DOI: 10.1039/d0na00503g
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced band modulation and excellent stability, transport and optical properties of penta-MP2 (M = Ni, Pd, and Pt) monolayers

Abstract: First principle calculations utilizing the density-functional theory are carried out to investigated the electronic properties, transport, and optical properties of the Penta-MP2 (M=Ni, Pd, and Pt) monolayer compounds under the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In the aspect of theory, DFT calculation revealed that uniaxial and biaxial strains can open up the bandgap of penta‐MP 2 (M = Ni, Pd, and Pt) monolayers. [ 184 ] The uniaxial tensile strain further reduced the structural symmetry of the pentagonal lattice, inducing anisotropic optical absorption. A study in GeP shows that the tensile strain is always more effective in modulating the optical anisotropy than the compressive strain, regardless of its direction.…”
Section: Modulation Of Optical Anisotropymentioning
confidence: 99%
“…In the aspect of theory, DFT calculation revealed that uniaxial and biaxial strains can open up the bandgap of penta‐MP 2 (M = Ni, Pd, and Pt) monolayers. [ 184 ] The uniaxial tensile strain further reduced the structural symmetry of the pentagonal lattice, inducing anisotropic optical absorption. A study in GeP shows that the tensile strain is always more effective in modulating the optical anisotropy than the compressive strain, regardless of its direction.…”
Section: Modulation Of Optical Anisotropymentioning
confidence: 99%
“…Here E(Ø) and EF are the electrostatic potential and Fermi level of the given system. The charge density difference was modelled by VESTA software [42,43].…”
Section: Dft Calculationsmentioning
confidence: 99%